Extreme Hypoxia Causing Brady-Arrythmias During Apnea in Elite Breath-Hold Divers - Kjeld, Thomas; Isbrand, Anders Brenøe; Linnet, Katrine; Zerahn, Bo; Højberg, Jens; Hansen, Egon Godthaab; Gormsen, Lars Christian; Bejder, Jacob; Krag, Thomas; Vissing, John; Bøtker, Hans Erik; Arendrup, Henrik Christian (Frontiers in Physiology, 2021)
Introduction The cardiac electrical conduction system is very sensitive to hypoglycemia and hypoxia and the consequence may be brady-arrythmias. Weddell Seals endure brady-arrythmias during their dives desaturating to 3.2 kPa and elite breath-hold-divers (BHD), who share metabolic and cardiovascular adaptions including bradycardia with diving mammals, endure similar desaturation during maximum apnea. We hypothesized that hypoxia causes brady-arrythmias during maximum apnea in elite BHD. Hence, this study aimed to define the arterial blood glucose (Glu), peripheral saturation (SAT), heart rhythm (HR) and mean arterial blood pressure (MAP) of elite BHD during maximum apneas. Methods HR was monitored with Direct-Current-Pads/ECG-lead-II and MAP and Glu from a radial arterial-catheter in nine BHD performing an immersed and head-down maximal static pool apnea after three warm-up apneas. SAT was monitored with a sensor on the neck of the subjects. On a separate day, 12-lead-ECG-monitored maximum static apnea was repeated dry (n=6). Results During pool apnea of maximum duration (385 ± 70 s) SAT decreased from 99.6 ± 0.5 to 58.5 ± 5.5 % (~PaO2 4.8 ± 1.5k Pa, P<0.001), while Glu increased from 5.8 ± 0.2 to 6.2 ± 0.2 mmol/l (P=0.009). MAP increased from 103 ± 4 to 155 ± 6 mm Hg (P<0.005). HR decreased to 46 ± 10 from 86 ± 14 beats/minute (p<0.001). HR and MAP were unchanged after 3-4 minutes of apnea. During dry apnea (378 ± 31 s) HR decreased from 55 ± 4 to 40 ± 3beats/minute (p=0.031). Atrioventricular dissociation and junctional rhythm were observed both during pool and dry apneas. Conclusion Our findings contrast with previous studies concluding that Glu decreases during apnea diving. We conclude during maximum apnea in elite BHD, that 1) the diving reflex is maximized after 3-4 minutes, 2) increasing Glu may indicate lactate metabolism in accordance with our previous results and 3) extreme hypoxia rather than hypoglycemia causes brady-arrythmias in elite BHD similar to diving mammals.